Boosting Predictive Models with Exception Rules - Lušková, Martina; Máša, Petr; Rauch, Jan, 1948-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This thesis presents a novel hybrid approach to predictive modelling that enhances logistic regression with exception rules. While regression-based models are widely used for their simplicity and generalisation ability, they often fail to capture localised, non-linear patterns. To address this limitation, the proposed algorithm integrates rule-based refinement into a standard logistic regression model by mining exception rules using the 4ft-Miner algorithm. These rules identify compact and interpretable subgroups in the data with elevated prediction confidence and are used to boost the baseline model. The hybrid model is implemented in Python and evaluated on the Telco Customer Churn dataset. The results show that while the overall predictive accuracy of the hybrid and baseline models is comparable, performance improved in uncertain prediction regions, instances where logistic regression predicted class probabilities near 0.5. Notably, some individual rules showed strong generalisation and substantially outperformed the baseline model in their respective subspaces. The design also incorporated techniques to prevent overfitting, including training-only rule mining, support constraints, and rule complexity limits. The findings confirm that boosting predictive models with exception rules is not only feasible but also beneficial in enhancing interpretability and performance.
Vedoucí práce: Petr Máša
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: informační management [obor dipl. práce]; diplomové práce; master's theses